2012
DOI: 10.11142/jicems.2012.1.3.295
|View full text |Cite
|
Sign up to set email alerts
|

Induction Motors Performance Study under Various Voltage Sags Using Simulation

Abstract: -The main aim of this paper is to study effects of different voltage sags and their intensity on the behavior of induction motors using a simulation approach. For this purpose, necessary simulation was done in Matlab -Simulink first. Then, to ensure-reasonable accuracy of the simulation, some results of the simulation were compared with the corresponding results measured in the laboratory. Then effects of intensity of symmetric voltage sag (three phase) and its starting point on the behavior of small and large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…In addition, the amplitude of the current waveform due to double phase sag has a higher value. Similar simulations are done in which the motor is under 85% of its rated load, but small increases in current is observed [29].…”
Section: B Asymmetrical Voltage Sagmentioning
confidence: 81%
“…In addition, the amplitude of the current waveform due to double phase sag has a higher value. Similar simulations are done in which the motor is under 85% of its rated load, but small increases in current is observed [29].…”
Section: B Asymmetrical Voltage Sagmentioning
confidence: 81%
“…3., it can be concluded that. 1) From [25] and [32], it can be concluded that current peak almost depends linearly on sag magnitude. However, as shown in Fig.…”
Section: A Effects Of Phase-angle Jump On Current Peakmentioning
confidence: 99%
“…In [24], a numerical algorithm is introduced for the approximate calculation of the current and torque peaks, and the mechanical speed loss for an extensive range of voltage sags and finds that the values of peak current and torque increase linearly with the decrease of voltage sag magnitude. In [25], the effects of different voltage sags are studied on the behaviors of induction motors by using a MATLAB/Simulink software. The consequences of unsymmetrical voltage sags on the torque and current peaks, and speed loss characteristics of three-phase squirrel-cage induction motor is analyzed based on the numerical algorithm in [26]- [28].…”
Section: Introductionmentioning
confidence: 99%